Tração mobilizada de reforços geossintéticos sob condições operacionais e efeito de umedecimento - Santos, Matheus Cardoso dos (2019)
The use of low permeability fine local soils instead of granular materials has been common in several countries due to the significant reduction of the costs associated with the transport of granular materials extracted from deposits. In fact, the use of fine soils may result in adequate behavior of reinforced soil structures under unsaturated conditions. However, in rainy periods, the strength and stifness of the structure can be affected and cause excessive deformation or even rupture. Although there are some observations on the effect of wetting on fine and geosynthetic soil behavior, few studies have quantified the effects of infiltration on mobilized tensile load and deformation. Thus, the present work aims to evaluate the effect of infiltration on the mobilized tensile load and deformations in layers reinforced with geosynthetics. For this purpose, an equipment called Load-transfer Soil to Geosynthetic System (LSGS) was developed, designed to simulate the actual mechanisms of action of a reinforced layer. The equipment simulates the mechanical response of the geosynthetic reinforcement under operational conditions in a reinforced layer with direct measurement of tensile-strain behavior under simultaneous conditions of overload and wetting. For the monitoring of the wetting front, the tests were instrumented with moisture sensors and tensiometers. In the tests, two different types of soil (well-graded sand and plastic sandy clay) and three geosynthetics (geogrid, woven geotextile and non-woven geotextile) were used. The results showed that the equipment simulated satisfactorily a layer reinforced with geosynthetics and allows to measure the tensile load behavior under operational conditions of reinforced soil walls with geosynthetics. The confinement increased the stiffness of the nonwoven geotextile three times but did not provide changes in the geogrid and the woven geotextile in both soils. The infiltration caused an increase in the deformations and the mobilized tensile load of the geogrid and woven geotextile and affected the resistance at the non-woven clay-geotextile soil interface significantly, so that the deformations resulting from the infiltration process were exponential.